Molecular phylogeny and intraspecific differentiation of the Trapelus agilis species complex in Iran (Squamata: Agamidae) inferred from mitochondrial DNA sequences - Shahamat, Ali-Ashgar; Wink, Michael (PeerJ, 2020)
Background Trapelus agilis consists of different morphotypes with restricted distributions in the Iranian Plateau. The phylogeny of the species complex has not been resolved so far, but recently Trapelus sanguinolentus were elevated from this complex into a full species. Other populations of the species complex need to be evaluated taxonomically. Methods In the present study, several populations of this species complex along with specimens of its closely related taxa in Iran, T. sanguinolentus, T. ruderatus and T. persicus, were examined using partial nucleotide sequences of two mitochondrial genes (cytb and ND2) (total length 1,322 bp). Result Populations of T. sanguinolentus clustered within the T. agilis species complex, thus indicating its paraphyly, but T. sanguinolentus was previously determined to be a species based on morphological features. The T. agilis species complex forms two distinct major clades, each of which is represented by several local populations on the Iranian Plateau. At least five distinct taxa can be identified within this traditional group. Our biogeographic evaluation of the molecular dataset suggested that the Trapelus complex originated in the Late Oligocene (30 mya) and subsequently diversified during the early to middle Miocene (22-13 mya). At first, the predominantly western clade of Trapelus ruderatus diverged from the other clades (22 mya). Afterward, Trapelus persicus diverged around 18 mya ago. The broader T. agilis complex started to diverge about 16 mya, forming several clades on the Iranian Plateau and in Central Asia. The different lineages within this species complex appear to be the result of vicariance events and dispersal waives. The corresponding vicariance events are the formation of the Zagros and Kopet Dagh basins (16-14 mya), and consequently, the aridification of the Iranian Plateau in the late Miocene (11-6 Mya).
Gesehen am 26.03.2020